National Eye Service (1929)
1929 1929 1920s 12 pages [9] NATIONAL EYE SERVICE provided at the following fixed prices :— White metal non-rusting spectacles, rimmed or rimless eye-glasses 7/6 Rolled Gold Spectacles, rimmed or rimless eyeglasses 15/- Imitation tortoiseshell spectacles, rolled gold and tortoiseshell spectacles and eyeglasses, rolled gold rimless spectacles 22/6 Bifocals, Toric or Crookes Lenses are extra. These fees and charges are the full cost of the service. Insured Persons and their dependants Many State-insured persons are entitled to ophthalmic benefit from their Approved Societies. They should apply to their Societies in accordance with their rules to be treated under this scheme, and if the approved Societies consent, generous grants towards the cost of the service may be obtained. The service is also available to all dependants of insured persons. Hospital Saving Association Contributors After taking into account the grants made by the Hospital Saving Association, the net charges to contributors and their dependants taking advantage of the service are as follows :— Solid Nickel Rolled Gold Where a new prescription is presented at the Clinic 3/9 7/6 Where an examination is made by the Surgeon at the Clinic and glasses are supplied to his prescription 10/- 17/6 When replacements of glasses in accordance with an old prescription are ordered 7/6 15/. 292/841.4/1/61